2015
DOI: 10.1152/ajpendo.00528.2014
|View full text |Cite
|
Sign up to set email alerts
|

New CETP inhibitor K-312 reduces PCSK9 expression: a potential effect on LDL cholesterol metabolism

Abstract: Despite significant reduction of cardiovascular events by statin treatment, substantial residual risk persists, driving emerging needs for the development of new therapies. We identified a novel cholesteryl ester transfer protein (CETP) inhibitor, K-312, that raises HDL and lowers LDL cholesterol levels in animals. K-312 also suppresses hepatocyte expression of proprotein convertase subtilisin/kexin 9 (PCSK9), a molecule that increases LDL cholesterol. We explored the underlying mechanism for the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…5). HR/AM-PRM performed on a quadrupole Orbitrap fi rst selects the peptide of interest and then fragments and scans all fragment ions simultaneously ( 7,8,45,47 ). Because PRM itself is a relatively recent method, MRM [sometimes referred to as selected reaction monitoring (SRM)] is the for the fi rst time.…”
Section: Discussionmentioning
confidence: 99%
“…5). HR/AM-PRM performed on a quadrupole Orbitrap fi rst selects the peptide of interest and then fragments and scans all fragment ions simultaneously ( 7,8,45,47 ). Because PRM itself is a relatively recent method, MRM [sometimes referred to as selected reaction monitoring (SRM)] is the for the fi rst time.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential causes of lowering LDL is reduction of PCSK9 levels as shown in the studies of anacetrapib and a new small CETP inhibitor (K-312) (35,36).…”
Section: Small and Dense Ldl Lp(a) And Proprotein Convertase Subtilimentioning
confidence: 99%
“…We generated an in vitro synthesized form of rabbit PCSK9 and used PRM to develop a rabbit PCSK9 spectral library and confirmed that K-312 did in fact lower circulating PCSK9 by >50%. 10, 25 Targeted proteomics has also been applied to in vivo metabolism studies of mostly LDL and HDL apolipoproteins during lipid-lowering clinical trials. Subjects are injected with amino acid tracer (D3-Leu), which is taken up by primarily the liver Most of these clinical metabolism studies have depended on SRM/MRM to detect very low levels of D3-Leu tracer incorporation into apolipoproteins.…”
Section: Selected Reaction Monitoring (Srm) and Parallel Reaction Monmentioning
confidence: 99%
“…21-23 Also, the less abundant proteins can be enriched by cellular fractionation methods such as those that separate cellular compartments or those that use immunopurification strategies ( Figure 1C). 24, 25 The dynamic range capabilities of MS continually improve, but the identification and quantification of low-abundance proteins still depend on sample preparation procedures that shift these low signals into the detection range of the instrument either by depletion and/or enrichment approaches.any developments in the field of proteomics have come from the yeast model system 1-3 and from cancer research ( Figure 1A). In addition, immortalized cells (eg, HeLa, HEK293T, RAW264.7, THP-1) have provided mass spectrometrists ample protein with limited variability across biological replicates, factors that are important to establish technical reproducibility when novel workflows are being developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation